2006
DOI: 10.1007/s00122-005-0193-y
|View full text |Cite
|
Sign up to set email alerts
|

QTL analysis of powdery mildew resistance in cucumber (Cucumis sativus L.)

Abstract: The name of the fifth author, M. Sugiyama, was rendered incorrectly in the original publication.The online version of the original article can be found at http:// dx

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 0 publications
1
27
0
Order By: Relevance
“…Transferability of SSRs between cucumber and melon has previously been indicated by cross-amplification and reciprocal mapping using cucumber and melon SSRs (e.g., Fazio et al 2003b, Gonzalo et al 2005, Sakata et al 2006, Fukino et al 2008b. In this study, we found amplified and polymorphic SSR markers that were present in both cucumber and melon, demonstrating the high transferability of our C. sativus SSRs to C. melo.…”
Section: Assessment Of Ssr Amplification and Polymorphismsupporting
confidence: 72%
See 1 more Smart Citation
“…Transferability of SSRs between cucumber and melon has previously been indicated by cross-amplification and reciprocal mapping using cucumber and melon SSRs (e.g., Fazio et al 2003b, Gonzalo et al 2005, Sakata et al 2006, Fukino et al 2008b. In this study, we found amplified and polymorphic SSR markers that were present in both cucumber and melon, demonstrating the high transferability of our C. sativus SSRs to C. melo.…”
Section: Assessment Of Ssr Amplification and Polymorphismsupporting
confidence: 72%
“…As has been the case in other cucurbit crops, molecular genetic technologies such as marker-assisted selection (MAS) will be highly desirable tools to support breeding, since cucumber cultivation generally requires much time, labor, space, and equipment. Recently, genetic markers have been successfully used to select morphological characteristics (Fan et al 2006) and disease resistance (Sakata et al 2006). The development of genetic markers associated with other economically important characteristics is eagerly anticipated by cucumber breeders.…”
mentioning
confidence: 99%
“…Brassica simple sequence repeat (SSR) markers (Lowe et al 2004, Suwabe et al 2002, Choi et al 2007, Ling et al 2007, Kim et al 2009) and Brassica sequence-tagged site (STS) markers (Kim et al 2006, Saito et al 2006, Choi et al 2007 were also used for the genotyping. The PCR reactions, detection of polymorphisms and construction of a linkage map were performed as described previously (Sakata et al 2006). A map of F 2 plants grown in 2005 was constructed using SSRs and STSs.…”
Section: Linkage and Qtl Analysesmentioning
confidence: 99%
“…The logarithm of odds (LOD) thresholds for each QTL (α = 0.05) were estimated as 3.7 and 3.3 in the 2007 and 2005 populations, respectively, by 1000 permutations. The QTL-linked AFLP fragments were cloned and sequenced for conversion into STS markers as described previously (Sakata et al 2006). The nucleotide sequences of the cloned AFLP fragments have been deposited to the DDBJ/EMBL/GenBank databases under accession nos.…”
Section: Linkage and Qtl Analysesmentioning
confidence: 99%
“…Linkage analysis studies indicate that the DM and PM genes are located either at the same locus or in closely linked loci (Fanourakis, 1984). The first quantitative trait loci (QTLs) for PM resistance in cucumber were identified by Sakata et al (2006) who mapped 5 QTLs in four linkage groups on an unsaturated linkage map.…”
Section: Introductionmentioning
confidence: 99%